Measurement of The Quality Employment Services - Khumaidi; Heri Sunarno (International Journal of Science, Technology & Management, 2021)
The focus of this research is industrial-based village areas, this research is focused on the quality of employment services, where the quality is measured by labor conditions, namely the fulfillment of the needs and expectations of local communities as service users for their absorption into industrial labor, in addition, it is measured by the dimension of service quality perception of provision. and service users. The results of the study explain two measuring tools in seeing the quality of employment services in industrial-based village areas.